Blood culture positivity and its clinical determinants among hospitalized male patients with newly diagnosed, laboratory-confirmed brucellosis: a hospital-based retrospective study - Han, Xue; Zhang, Ruiqing; Xu, Bianxia; Zhang, Weijie; Wang, Fang; Yuan, Beibei; Ma, Quanlong; Ma, Jing; Zhu, Zhenhua; Shan, Xiaofang; Liu, Ye (Frontiers in Microbiology, 2026)
Background and objectiveBrucellosis is a common zoonotic disease worldwide. Because its symptoms are non-specific and laboratory findings vary, diagnosis remains challenging. Blood culture is still the gold standard for confirmation, but its yield is often limited. This study aimed to estimate blood-culture positivity among hospitalized male patients with newly diagnosed brucellosis and to identify clinical and laboratory factors independently associated with culture positivity within confirmed cases.MethodsWe conducted a hospital-based retrospective study of 1,188 hospitalized men with newly diagnosed brucellosis admitted to a tertiary infectious-disease hospital in China between 2021 and 2023. Demographics, clinical manifestations, laboratory parameters, and blood-culture results were collected. Multivariate logistic regression was used to identify independent predictors of a positive blood culture.ResultsThe overall blood-culture positivity rate was 30.9%. Univariate analysis indicated that disease stage, fatigue, fever, anorexia, splenomegaly, arthritis, paraspinal abscess, joint effusion, platelet count (PLT), alanine aminotransferase (ALT), aspartate aminotransferase (AST), gamma-glutamyl transferase (GGT), albumin (ALB), total bilirubin, lactate dehydrogenase (LDH), serum agglutination test (SAT), procalcitonin (PCT), and erythrocyte sedimentation rate (ESR) were associated with culture positivity. After multivariate adjustment, LDH, SAT, PCT, and ESR emerged as independent predictors of a positive blood culture, with PCT showing the strongest predictive value. Higher levels of LDH, SAT, PCT and ESR were independently associated with higher positive rates of blood cultures.ConclusionIn this hospital-based retrospective cohort of confirmed brucellosis, LDH, SAT titer, PCT, and ESR were independently associated with blood-culture positivity. These routinely available parameters may help risk-stratify bacteremic likelihood and support culture-related decision-making (e.g., prioritizing sampling and considering repeat cultures when clinically warranted) among SAT-positive (or otherwise confirmed) patients, but they should not be interpreted as standalone markers for diagnosing Brucella bacteremia without microbiological confirmation.